Пошаговое объяснение:
А)
3|2х - 4| = 18
|2х - 4| = 18 : 3
|2х - 4| = 6
1)
2х - 4 = 6
2х = 6 + 4
2х = 10
х = 10 : 2
х = 5
х1 = 5
2)
2х - 4 = -6
2х = -6 + 4
2х = -2
х = -2 : 2
х = -1
х2 = -1
ответ: 5; -1.
Б)
10|х| - 2|х| - 5 = 4|х|
10|х| - 2|х| - 4|х| = 5
4|х| = 5
|х| = 5 : 4
|х| = 1,25
х1 = 1,25
х2 = -1,25
А.312x - 41 = 18
12x - 41 18:3
12x - 41 = 6
1.2x - 4 = 6
2x = 6 + 4
2x = 10
x = 10:2
x = 5
x1 = 5
2.2x - 4 = -6
2x = -6 + 4
2x = -2
x = -2:2
x = -1
x2 = -1
Б.10|x| - 2|x| - 5 = 4|x|
10|x| - 2|x| - 4|x| = 5
4|x| = 5
|x| = 5 : 4
|x| = 1,25
x1 = 1,25
х2=-1,25
Пошаговое объяснение:
А)
3|2х - 4| = 18
|2х - 4| = 18 : 3
|2х - 4| = 6
1)
2х - 4 = 6
2х = 6 + 4
2х = 10
х = 10 : 2
х = 5
х1 = 5
2)
2х - 4 = -6
2х = -6 + 4
2х = -2
х = -2 : 2
х = -1
х2 = -1
ответ: 5; -1.
Б)
10|х| - 2|х| - 5 = 4|х|
10|х| - 2|х| - 4|х| = 5
4|х| = 5
|х| = 5 : 4
|х| = 1,25
х1 = 1,25
х2 = -1,25
А.312x - 41 = 18
12x - 41 18:3
12x - 41 = 6
1.2x - 4 = 6
2x = 6 + 4
2x = 10
x = 10:2
x = 5
x1 = 5
2.2x - 4 = -6
2x = -6 + 4
2x = -2
x = -2:2
x = -1
x2 = -1
ответ: 5; -1.
Б.10|x| - 2|x| - 5 = 4|x|
10|x| - 2|x| - 4|x| = 5
4|x| = 5
|x| = 5 : 4
|x| = 1,25
x1 = 1,25
х2=-1,25